ANALISIS TINGKAT KEPUASAN SISTEM INFORMASI PENCATATAN DAN PENAGIHAN BIAYA REKENING AIR PELANGGAN PDAM MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) - Muhammad Anwar; Muhammad Azisan (Universitas Negeri Padang, 2019)
This study aims to examine the effect of the End User Computing Satisfaction variable on user satisfaction of the information system application. Recording and collection of customer water costs for PDAM Kota padang. This analysis uses independent variables, namely content, accuracy, format, easy of use, and timeliness. the application user satisfaction. Samples of this research are PDAM employees: billing, service, cashier, finance, IT and director directors and recording records. Samples were conducted using the proportionate stratified random method. Data collection was done by questionnaires distributed directly to respondents 78 questionnaires. Instead it was distributed to PDAM employees by measuring using a Likert scale after it was tested for validity and reliability. Data analyzed would use a questionnaire questionnaire. Samples were taken at PDAM Kota Padang. Statistical methods used Multiple Linear Regression Analysis. The results of the analysis of a data show: All instruments on EUCS simultaneously have an influence in recording and collection of water costs for PDAM customers. The use of EUCS has a significant effect on the recording and collection of customer water costs at PDAM Padang City.